1955
DOI: 10.1136/bmj.1.4915.708
|View full text |Cite
|
Sign up to set email alerts
|

Foster Kennedy Syndrome Produced by Myelomatous Deposits in the Skull

Abstract: MEDICAL JC)URNAL normal pressure, with one cell per c.mm. and a protein content of 32 mg. per 100 ml. The blood Wassermann reaction was negative. The electroencephalogram showed rather excessive low amplitude, slow activity.At operation (Mr. N. 0. K. Gibbon) on February 28 a single plum-coloured growth the size of a pea was_jound in the head of the pancreas and removed without undue difficulty. Convalescence was uneventful. Post-operative hyperglycaemia was not observed, the fasting blood-sugar values falling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Less commonly, intracranial extramedullary plasmacytomas compress the cerebral hemispheres, inducing seizures 24. In addition, multiple cranial neuropathies associated with extramedullary plasmacytomas, such as occurred in our patient, usually present as late manifestations of the disease and carrying a worse prognosis 1013. However, despite such deranged laboratory data in our patient, it was an initial presentation leading to a diagnosis of multiple myeloma.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Less commonly, intracranial extramedullary plasmacytomas compress the cerebral hemispheres, inducing seizures 24. In addition, multiple cranial neuropathies associated with extramedullary plasmacytomas, such as occurred in our patient, usually present as late manifestations of the disease and carrying a worse prognosis 1013. However, despite such deranged laboratory data in our patient, it was an initial presentation leading to a diagnosis of multiple myeloma.…”
Section: Discussionmentioning
confidence: 57%
“…Isolated cranial neuropathies such as optic neuropathy, oculomotor nerve palsy, trigeminal neuropathy, abducens nerve palsy, facial palsy and hypoglossal neuropathy have been reported as neurological symptoms of solitary extramedullary plasmacytomas 49. Nevertheless, cranial neuropathies such as Foster–Kennedy syndrome, cavernous sinus syndrome, Gradenigo syndrome and jugular foramen syndrome have also been reported as manifestations of late-stage MM 1013. Tolosa–Hunt syndrome is an idiopathic granulomatous inflammatory disease of cavernous sinus, which usually demonstrates painful ophthalmoplegia with variable degree of ophthalmic and maxillary nerves involvement 14.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple cranial neuropathies in combination such as Foster Kennedy syndrome, cavernous sinus syndrome, Gradenigo syndrome and jugular foramen syndrome had been reported in late stages of MM. [3][4][5] Multiple CNs involvements as the initial presentation for plasmacytoma had been reported very rarely only. [6][7][8]11] Ko et al [6] reported a case of the intracranial plasmacytoma in the cavernous sinus presented as left IV and partial V CN palsy.…”
Section: Discussionmentioning
confidence: 98%
“…[2] Multiple cranial neuropathies had been reported in late stages of MM. [3][4][5] Very rarely multiple cranial nerves (CN) involvement by plasmacytoma may be presenting feature of MM. [6][7][8] Here, we report a case of multiple CN palsy (right 3 rd , 6 th , 9 th , 10 th and 12 th CNs) as first presentation of the intracranial plasmacytoma.…”
Section: Introductionmentioning
confidence: 99%
“…The multiple cranial neuropathies in combination such as Foster Kennedy syndrome, cavernous sinus syndrome, Gradenigo syndrome and jugular foramen syndrome had been reported in late stages of MM. [6,7,8] Multiple CNs involvements as the initial presentation for plasmacytoma had been reported very rarely. [3,4,5] Ko et al reported a case of the intracranial plasmacytoma in the cavernous sinus presented as left 6th and partial 5 th CN palsy.…”
Section: Case Reportmentioning
confidence: 99%